2017
DOI: 10.1152/ajprenal.00579.2016
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α activation improves renal oxygenation and mitochondrial function in early chronic kidney disease

Abstract: The pathophysiology of chronic kidney disease (CKD) is driven by alterations in surviving nephrons to sustain renal function with ongoing nephron loss. Oxygen supply-demand mismatch, due to hemodynamic adaptations, with resultant hypoxia, plays an important role in the pathophysiology in early CKD. We sought to investigate the underlying mechanisms of this mismatch. We utilized the subtotal nephrectomy (STN) model of CKD to investigate the alterations in renal oxygenation linked to sodium (Na) transport and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 59 publications
2
35
0
Order By: Relevance
“…According to a research conducted by Tan et al [26], SAL may represent a novel therapeutic agent for the treatment and prevention of hypoxia and oxidative stress-related diseases via targeting HIF-1α, indicating the possible target of SAL in FSGS. HIF-1α is activated under hypoxia and promotes expression of genes involved in cell fate, angiogenesis, and glucose metabolism [11,12]. Zhang et al [27] have reported that blocking HIF-1α could inhibit the activation of both inflammatory response and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a research conducted by Tan et al [26], SAL may represent a novel therapeutic agent for the treatment and prevention of hypoxia and oxidative stress-related diseases via targeting HIF-1α, indicating the possible target of SAL in FSGS. HIF-1α is activated under hypoxia and promotes expression of genes involved in cell fate, angiogenesis, and glucose metabolism [11,12]. Zhang et al [27] have reported that blocking HIF-1α could inhibit the activation of both inflammatory response and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factor-1α (HIF-1α) is activated under hypoxia and promotes expression of genes involved in cell fate, angiogenesis, and glucose metabolism [11,12]. HIF-1α plays a crucial role in pathogenesis of chronic kidney disease (CKD).…”
Section: Introductionmentioning
confidence: 99%
“…Another hypothesis is that mitochondria dysfunction in CKD relates to haemodynamic adaptations, due to an oxygen supply‐demand mismatch with resulting hypoxia and activation of hypoxia‐inducible factor 1 (HIF‐1). This lowers mitochondrial oxygen consumption and superoxide production and increase mitochondrial volume density . Moreover, the uraemic toxin indoxyl sulphate generated from gut microbiota decreases the expression of PGC‐1α and increases autophagy in skeletal muscle .…”
Section: Mitochondrial Dysfunction In Kidney Diseasementioning
confidence: 99%
“…This lowers mitochondrial oxygen consumption and superoxide production and increase mitochondrial volume density. 45 Moreover, the uraemic toxin indoxyl sulphate generated from gut microbiota decreases the expression of PGC-1α and increases autophagy in skeletal muscle. 5,38,40,43,[46][47][48] Lastly, since deficiency of essential minerals can accelerate mitochondrial decay, 49 iron deficiency is a common and clinically important concern in CKD.…”
Section: Mitochondrial Dysfunction In Kidney Diseasementioning
confidence: 99%
“…For example, Li et al [9] demonstrated that EGCG could inhibit IGF-I-stimulated lung cancer angiogenesis through the down-regulation of HIF-1α and VEGF expression; Luo et al [10] verified that EGCG decreases the expression of HIF-1α and VEGF and cell growth in MCF-7 breast cancer cells. HIF-1α is activated under hypoxia and promotes expression of genes involved in cell fate, angiogenesis and glucose metabolism [11,12]. Some researches indicated that over-activation of HIF-1α promotes fibrosis and contributes to the development of CKD [13].…”
Section: Introductionmentioning
confidence: 99%